PENGARUH KOMITMEN, PERSEPSI, DAN PENERAPAN PILAR DASAR TOTAL QUALITY MANAGEMENT TERHADAP KINERJA MANAJERIAL - Pasaribu, Hiras (Jurnal Akuntansi dan Keuangan Indonesia, 2009)
This research means to discover the influence o f top management commitment and the perception o f division manager about total quality management (TQM) and the implementation o f fundamental base o f it toward to the effectiveness of the quality cost control (QCC) and its implication to the managerial performance at BUMN (state owned company) manufacturers in Indonesia. Population method survey is implemented to 28 BUMN manufacturers in Indonesia. The data used are primary and secondary data. Then, the hypothesis is tested using path analysis. The results show that: 1) Top management commitment and perceptions of division managers have no significant relationship with the application o f the basic pillars o f Total Quality management in BUMN manufacturer. (2) Simultaneously and partially, the commitment o f top management, the perception o f division manager, and the implementation of fundamental base o f TQM have influence toward the effectiveness of QCC; and (3) The implications o f both simultaneously and partially o f commitment of top management, the perception of division manager, the implementation o f fundamental base o f TQM, and the effectiveness of QCC influence the managerial performance.